Nanoclay Reinforced Polymer Composites Natural Fibre/Nanoclay Hybrid Composites - Jawaid, Mohammad; Qaiss, Abou el Kacem; Bouhfid, Rachid; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2016)
This book highlights the most essential advances in nanoclay-based nanocomposites, especially natural fibre-reinforced polymer composites. Readers will find extensive information on nanoclay from preparation to applications, and the characterization techniques needed in order to evaluate the resulting properties of nanoclay-based natural fibre-reinforced polymer composites. Topics covered include the characterization of nano-sized clay, chemical modification, and processing techniques for nanocomposites from nanoclay. The book offers a valuable reference guide for academics and industrial practitioners alike.
Recent advances in nanoclay/Natural fibre based Hybrid Composites -- Nanoclay based natural fibre reinforced polymer composites: Mechanical and Thermal properties -- Processing techniques of nanoclay based natural fibre reinforced polymer composites -- Effect of nanoclay on natural fiber/polymer composites -- Effect of Nanoclay on the Mechanical Performance of Cellulose Particulate Reinforced Polymer Composites Manufactured by JMFIL Process -- Effects of Micro- and Nano- Cellulose on Tensile and Morphological Properties of Montmorillonite Nanoclay Reinforced Polylactic Acid Nanocomposites -- Nanoclay and natural fibers based hybrid composites: Mechanical, morphological, thermal and rheological properties -- Mechanical Performance of Nanoclay/natural fibre reinforced polymer composites -- Tribiological properties of natural fibre/Nanoclay composites -- Hybrid composite foams based on nanoclays and natural fibres -- Effect of Plasticizer on Fracture Toughness of Polylactic Acid (PLA)/ Kenaf Fiber (KF)/ Montmorillonite organoclay (MMT) Hybrid Biocomposite.
Keywords: Ceramic materials; Polymers; Materials; Ceramics; Polymers; Materials Engineering